Future brain : the 12 keys to create your high-performance brain - Brockis, Jenny (John Wiley and Sons Australia, 2016)
Super-charge your brain to gain a huge competitive edge in business and in life Future Brain is the busy professional's secret weapon for boosting mastery, efficiency, and productivity to gain that coveted competitive edge - in business and in life. Designed to be implemented at the individual, team, or organisational level, this in-depth, step-by-step framework leverages neuro-scientific principles to help you develop a solid, habit-changing plan for building and maintaining brain fitness and healthy behaviours. Author Dr. Jenny Brockis will help you develop your thought processes and your r.